An energy-resolving photon-counting X-ray detector for computed tomography combining silicon-photomultiplier arrays and scintillation crystals - Kenji Shimazoe; Donghwan Kim; Moh Hamdan; Yosuke Kobayashi; Kei Kamada; Masao Yoshino; Yasuhiro Shoji; Kyohei Sakamoto; Fabio Acerbi; Alberto Gola (Communications Engineering)
Abstract X-ray photon-counting computed tomography (PCCT) has garnered considerable interest owing to its low-dose administration, high-quality imaging, and material decomposition characteristics. Current commercial PCCT systems employ compound semiconductor photon-counting X-ray detectors, which offer good energy resolution. However, the choice of materials is limited, and cadmium telluride or cadmium zinc telluride is mostly used. Although indirect radiation detectors can be used as alternatives to compound semiconductor detectors, implementing fine-pitch segmentation in such detectors is challenging. Here we designed an indirect fine-pitch X-ray photon-counting detector by combining miniaturized silicon photomultiplier arrays and fast scintillation crystals, with a pixel size of 250 µm, for future indirect PCCT. The fabricated array detector has the potential to discriminate photon energies with a 27% resolution at 122 keV, 296 µm spatial resolution, and charge-sharing inhibition ability.